Pertumbuhan dan Produksi Galur-Galur Padi Toleran Fe Generasi F8 Hasil Persilangan IR64 x Hawara Bunar di Lahan Pasang Surut, Banyuasin, Sumatera Selatan - LA KOLAKA; MUNIF GHULAMAHDI; . MIFTAHUDIN (Jurnal Sumberdaya Hayati, 2015)
Utilization of marginal lands such as tidal land should be done to increase rice production as a solution of the decreasing productive land. However, rice cultivation in such land will be affected by low soil fertility, soil acidity and Fe toxicity. Fe-tolerant varieties are needed to overcome those problems. The objective of the research was to analyze the growth and production of Fe tolerant rice lines in tidal soil type C, Banyuasin, South Sumatera. Screening for Fe-tolerant character of 54 rice lines from the F8 RIL population derived from a cross between rice var. IR64 and var. Hawara Bunar using hydroponic technique under 1000 ppm Fe resulted 25 Fe-tolerant lines. The field test of 25 putative tolerant rice lines, at the tidal land in Banyuurip, Banyuasin, showed that the most lines grew better than that of var. Hawara Bunar parent. Several lines produced yield higher than that of var. Hawara Bunar parent. The field experiment resulted two rice lines, which were IRH108 and IRH195 that potential for further studies.